Social tipping points and Earth systems dynamics - Bentley, R. A.; Maddison, Eleanor J.; Ranner, P. H.; Bissell, John; Caiado, Camila C. S.; Bhatanacharoen, Pojanath; Clark, Timothy; Botha, Marc; Akinbami, Folarin; Hollow, Matthew; Michie, Ranald; Huntley, Brian; et al. (Frontiers in Environmental Science, 2014)
Recently, Early Warning Signals (EWS) have been developed to predict tipping points in Earth Systems. This discussion highlights the potential to apply EWS to human social and economic systems, which may also undergo similar critical transitions. Social tipping points are particularly difficult to predict, however, and the current formulation of EWS, based on a physical system analogy, may be insufficient. As an alternative set of EWS for social systems, we join with other authors encouraging a focus on heterogeneity, connectivity through social networks and individual thresholds to change.